2016
DOI: 10.3389/fcvm.2016.00034
|View full text |Cite
|
Sign up to set email alerts
|

Rat Heterotopic Heart Transplantation Model to Investigate Unloading-Induced Myocardial Remodeling

Abstract: Unloading of the failing left ventricle in order to achieve myocardial reverse remodeling and improvement of contractile function has been developed as a strategy with the increasing frequency of implantation of left ventricular assist devices in clinical practice. But, reverse remodeling remains an elusive target, with high variability and exact mechanisms still largely unclear. The small animal model of heterotopic heart transplantation (hHTX) in rodents has been widely implemented to study the effects of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
2
12
0
Order By: Relevance
“…It should be noted that heterotropic rat heart transplantation has been considered to be a relevant model to mimic unloading-induced changes in the failing heart, especially for investigating molecular mechanisms of myocardial remodelling. 1 Our data regarding the increased activities of sarcolemmal Ca 2þ pump and Na þ -Ca þ exchange activities can thus be seen to serve as an adaptive mechanism for the maintenance of intracellular Ca 2þ concentration in heterotopic transplanted heart and support the view that unloading of the failing left ventricle plays a critical role for the improvement of heart function. It is also likely that the reversal of cardiac remodeling and improved heart function in failing hearts due to myocardial infarction upon treatments with diverse interventions, such as losartan, prazosin, and metoprolol may be occurring through unloading of the left ventricle and subsequent reduction is the ventricular wall tension.…”
Section: Discussionsupporting
confidence: 72%
“…It should be noted that heterotropic rat heart transplantation has been considered to be a relevant model to mimic unloading-induced changes in the failing heart, especially for investigating molecular mechanisms of myocardial remodelling. 1 Our data regarding the increased activities of sarcolemmal Ca 2þ pump and Na þ -Ca þ exchange activities can thus be seen to serve as an adaptive mechanism for the maintenance of intracellular Ca 2þ concentration in heterotopic transplanted heart and support the view that unloading of the failing left ventricle plays a critical role for the improvement of heart function. It is also likely that the reversal of cardiac remodeling and improved heart function in failing hearts due to myocardial infarction upon treatments with diverse interventions, such as losartan, prazosin, and metoprolol may be occurring through unloading of the left ventricle and subsequent reduction is the ventricular wall tension.…”
Section: Discussionsupporting
confidence: 72%
“…First, they support our main thesis that cardiac atrophy is the most serious harmful effect of prolonged mechanical unloading which, even in the face of the sound evidence on molecular and structural ‘reverse remodeling’ after LVAD application [ 4 , 6 , 11 , 15 , 30 ], could limit successful outcomes of such treatment in terms of functional cardiac recovery and possible weaning from LVAD treatment.…”
Section: Discussionsupporting
confidence: 61%
“…Using an array of imaging and functional assessment techniques these workers showed that despite considerable atrophy, the intrinsic contractile properties of the myocardium apparently remained normal [ 4 , 14 , 15 , 17 , 19 , 20 , 25 , 30 , 35 , 51 ]. In addition, quantitative histologic studies showed that cardiac atrophy after HT x is due to the loss of volume of existing myocytes without any significant change in their number [ 15 , 29 , 35 , 42 , 50 ]; therefore cardiac atrophy is considered the most detrimental effect of prolonged heart unloading [ 4 , 9 , 11 , 14 , 15 , 22 , 30 , 51 ]. Since a close relationship between the decrease in the myocyte volume and of the heart mass has been clearly shown [ 15 , 29 , 47 , 50 ], it is commonly accepted that ‘unsophisticated’ markers such as whole heart, LV and RV weights, when compared with the respective values in the recipient, are reliable indices of the function of the heart exposed to long-term unloading after HT x [ 11 , 30 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations